THE AUTHENTICITY OF ENGLISH LANGUAGE ASSESSMENT FOR THE TWELFTH GRADERS OF SMK(VOCATIONAL HIGH SCHOOL) NEGERI 4 SURAKARTA - Nurul Hidayati (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2016)
The new curriculum applied in Indonesia recommended the use of authentic assessment. This study deals with the authenticity of English assessment. This research aims at finding empirical facts about what type of assessments are used, describing the authenticity of the assessments, showing teachers’ understanding to the assessment system and identifying problems encountered in applying authentic assessment. The method used is qualitative research, and the data was collected by observation, interview and content analysis. The findings are firstly, the teacher used three types of assessment : (a) Formative Test covering affective-cognitive-psychomotoric aspects (b) Mid Term Test (c) Semester Test. Secondly, the Formative Test had high level of authenticity, while the Mid Term Test and Semester Test had low authenticity. Thirdly, the scoring system used was the Criterion Reference Test which refers to Minimum Mastery Criteria. (4) There were at least four problems in applying authentic assessment : (a) the teacher felt overburdened with too many assessment formats (b) the inconsistency in regulation cause confusion for teachers (c) insufficient learning facilities caused ineffectivity (d) insufficient IT system needed improvement. The school had been doing efforts to overcome the problems.